STRATEGI PENINGKATAN PRODUKSI BERAS MELALUI PENEKANAN SUSUT PANEN DAN PASCAPANEN DENGAN PENDEKATAN SISTEM MODELING: STUDI KASUS KABUPATEN INDRAMAYU, JAWA BARAT - Somantri, Agus S.; Luna, Prima; Kamal, Irpan Badrul (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Paddy loss during harvest and postharvest handling is a complicated system involving many elements, and they are inter-connected. Therefore, to overcome these issues, appropriate and sustainable strategies should be implemented. The purpose of this study was to analyze the leverage factors that can overcome the problems of post-harvest losses of rice by a dynamic system approach as a basis in formulating policy strategy. This research was conducted in Indramayu, West Java, from January to December 2012. The methodology used in this research was modelling system approach. Primary data collection was conducted by a questionnaire survey and interviews with stakeholders and farmers as respondents. Secondary data collection was obtained from the Central Bureau of Statistics Centre (Jakarta) and regional (West Java), Regional Agriculture Services, Regional Industrial and Trade Services, Regional Population and Civil Registration Agency, Center for Agricultural and Food Security Agency. The results showed that the reduction of rice losses could be approached in two ways: technical approach and cultural approach. The technical approach could be developed by implementing a quality management system such as GHP and GMP, while the cultural approach could be implemented by creating new jobs. Application of the quality system would also encourage the revitalization in rice milling so that it would increase the yield, and so the application of the quality management system would contribute greatly to the production of dry unhulled rice as well as rice in Indramayu. The implementation of this strategy must consider the ability and readiness of the district, so that the strategies could be more realistic and easier to be implemented. The simulation results showed that the implementation of the strategy by using harvest and postharvest equipments to be accompanied by the implementation of GHP and GMP, may decrease shrinkage ranging from 5.58% to 10.14%, or the equivalent of rescuing MPD from 61,240 to 115,859 tons in 2020.